Answer:
[tex] E(100 Y^2) =100 E(Y^2)[/tex]
And we have that :
[tex] E(Y^2) =\sum_{i=1}^n X^2_i P(X_i)[/tex]
And replacing we got:
[tex] E(Y^2) =0^2 *0.6 + 1^2 *0.25 +2^2*0.10 +3^2 *0.05 = 1.1[/tex]
And finally we have:
[tex] E(100 Y^2) =100 *1.1 = 110[/tex]
Step-by-step explanation:
For this case we have the following probability masss function given:
Y 0 1 2 3
p(Y) 0.6 0.25 0.10 0.05
And we can define the surcharge with this expression [tex] 100Y^2[/tex]
We want to find the expected value for the last expression and we can do it on this way:
[tex] E(100 Y^2) =100 E(Y^2)[/tex]
And we have that :
[tex] E(Y^2) =\sum_{i=1}^n X^2_i P(X_i)[/tex]
And replacing we got:
[tex] E(Y^2) =0^2 *0.6 + 1^2 *0.25 +2^2*0.10 +3^2 *0.05 = 1.1[/tex]
And finally we have:
[tex] E(100 Y^2) =100 *1.1 = 110[/tex]